2017
DOI: 10.1016/j.jim.2017.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Human immune compartment comparisons: Optimization of proliferative assays for blood and gut T lymphocytes

Abstract: The accumulation of peripheral blood late-differentiated memory CD8 T cells with features of replicative (cellular) senescence, including inability to proliferate in vitro, has been extensively studied. Importantly, the abundance of these cells is directly correlated with increased morbidity and mortality in older persons. Of note, peripheral blood contains only 2% of the total body lymphocyte population. By contrast, the gut-associated lymphoid tissue (GALT) is the most extensive lymphoid organ, housing up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Using the BrdU proliferation assay, 25 we confirmed that optimal responses were obtained at day 3 when PBMC cultures were exposed to the mitogen PHA and by 5 days when cultured with SEA or SWAP. Cultures from those optimum response days are presented in Figure 5 .…”
Section: Resultssupporting
confidence: 56%
“…Using the BrdU proliferation assay, 25 we confirmed that optimal responses were obtained at day 3 when PBMC cultures were exposed to the mitogen PHA and by 5 days when cultured with SEA or SWAP. Cultures from those optimum response days are presented in Figure 5 .…”
Section: Resultssupporting
confidence: 56%
“…We tested the proliferative capacity of CD3/CD28/CD2-stimulated blood and gut derived mononuclear cells in 5-day cultures. For each donor, both stimulated and unstimulated (control) cultures were evaluated, using our recently developed double-label CSFE/BrdU system [ 28 ]. Briefly, proliferating cells registered as CFSE lo BrdU + and non-proliferating cells CFSE hi BrdU - ( Fig 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…Proliferation status of CD8 + T cells was determined using a recently developed double-label CFSE/BrdU system on 5-day cultures of blood and gut derived mononuclear cells stimulated with CD3/CD28/CD2 antibodies, as previously described in extensive detail [ 28 ]. On day 5, live CD8 + T cells from blood and gut cultures that had undergone proliferation following stimulation were identified as CFSE low BrdU + .…”
Section: Methodsmentioning
confidence: 99%
“…The generally favorable safety profile of anti-CD20 therapies may be due to several factors. First, although B cell depletion from the circulation is nearly complete, only 2% of the body’s total lymphocyte pool exists in peripheral blood, 91 and depletion of the body’s major stores of B cells in lymphoid organs is only partial. Thus, a large reservoir of B lymphocytes likely remain, even after multiple doses.…”
Section: Anti-cd20 Therapymentioning
confidence: 99%